Heterogeneities in the latent functions of employment: New findings from a large-scale German survey - Bähr, Sebastian; Batinic, Bernad; Collischon, Matthias (Frontiers in Psychology, 2022)
Building on psychologist Marie Jahoda's pioneering work, the psychological literature has shown that work fulfills both manifest functions (e.g., monetary returns) and latent functions (e.g., social contact). This paper uses data from the German panel study "Labor market and social security" (PASS), which contains information on latent and manifest factors (from a shortened latent and manifest benefits, or LaMB, scale) as well as a large array of other variables for over 9,000 respondents. This probability-sampled data allows for detailed analyses that have not previously been possible. We investigate differences in these factors by labor market status, among those employed, and among those unemployed. We identify considerable variation between status groups, suggesting that employment overall is important and that longer periods of unemployment lead to a gradual decay of the latent and manifest factors. Furthermore, regression analyses show that the LaMB measures account for approximately 70% of the partial correlations between unemployment and various well-being measures.